PENGARUH CITRA MEREK, KUALITAS PRODUK, DAN PROMOSI PENJUALAN TERHADAP KEPUTUSAN PEMBELIAN YAMAHA NMAX: Studi Di Kecamatan Jagakarsa Jakarta Selatan - Bagus Siswanto, - (2019)
This research is a quantitative research that aims to determine the influence of brand image, product quality andsales promotion to purchase decision Yamaha Nmax. The population in this study was the community of KecamatanJagakarsa South Jakarta. The sample size was taken 75 respondents, with non probability sampling method, especially purposive sampling. Data collection was done through questionnaires. Analytical technique used is the method of analysis PLS (Partial Least Square). The results of this study indicate that (1) brand image has a significant influence onpurchase decision with coefficient value of 0,579.(2) product quality has a significant on purchase decisionwith coefficient value of 0,338.(3) sales promotion has no effect a significantinfluence on purchase intention with coefficient value of -0,002